Pendampingan Edukasi Pembuatan Minyak Goreng Murni Pada Petani Kelapa - Nuraisyah, Fatma; Praja, Apik Rusdiarna Indra; Anwar, Nuril (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2023)
Coconut plant is a plant that is useful for everyday life. These plants can be used by the community starting from the roots to the tips of the leaves, this is what makes coconut plants have high economic value. Some areas in Indonesia make coconut as a source of livelihood, one of which is in the Province of the Special Region of Yogyakarta, Kab. KulonProgo, Kec. Kokap, Dusun Tangkisan II. Based on the local natural resources they have, the majority of the local people's livelihood is selling coconuts but what is sold is still raw. The purpose of this service is to improve soft skills as a stimulation of the independence of making coconut oil through a group of coconut farmers in Tangkisan II Hamlet. This activity method uses a questionnaire instrument by analyzing the average value of the pre-posttest results on coconut farmers. Result: there is a difference in the mean value of the pretest. Conclusion: the group of housewives is able to make and process coconut into pure cooking oil so that it has economic value and increases household income.